Kyrgyz Republic : Overview of Climate Change Activities - World Bank (Washington, DC, 2014)
This overview of climate change activities in the Kyrgyz Republic is part of a series of country notes for five Central Asian countries that summarize climate portfolio in a number of sectors, namely agriculture, forestry, water, health, energy, and transport. Recognizing the nature and significance of climate change contribution to an increase in disaster risk, the note also looks into the development partners' approaches and measures in this area. This note further provides a brief overview of the Kyrgyz Republic climate context in terms of observed impacts and historical trends as well as climate projections specific to sectors that are considered to be essential to the country's economic development. Finally, the note assesses national policy and institutional context related to climate change as well as suggests potential ways forward that can help the Kyrgyz Republic mainstream climate considerations into development activities and planning and create public demand for climate actions.